Urethral diverticulum carcinoma in females—a case series and review of the English and Japanese literature - O’Connor, Eabhann; Iatropoulou, Domniki; Hashimoto, Sho; Takahashi, Satoru; Ho, Daniel Heffernan; Greenwell, Tamsin (Translational Andrology and Urology; Vol 7, No 4 (August 15, 2018): Translational Andrology and Urology (Male Genitourinary Reconstruction and Trauma), 2018)
The aims of our study were to describe our case series of three urethral diverticulum carcinomas (UDC) in women and to review the literature on UDC in females to determine patient characteristics, presenting symptoms and outcomes along with optimal investigations and treatment modalities. A literature search was performed utilizing Medline, EMBASE and the Cochrane library for all papers including case reports on UDC in women published to date. The results along with those of our three cases are detailed. A total of 126 cases of UDC in women have been reported; 75% adenocarcinoma (Adenoca), 15% transitional cell carcinoma (TCC) and 10% squamous cell carcinoma (SCC). Median age at presentation was 53 years (range, 14–81 years). The commonest presenting symptoms were bleeding and retention. Cystoscopy, MRI and trans-urethral biopsy were the commonest methods of diagnosis. Treatment was radiotherapy +/− chemotherapy alone in 21%, local excision +/− radiotherapy in 44%, urethrectomy in 3% and anterior exenteration +/− radiotherapy in 32%. At last follow-up 63% were alive and well, 10% were alive with recurrent cancer and 25% had died from their disease. UDC is rare in women. It is predominantly adenocarcinoma. There is no established treatment and survival is at best moderate. An international registry and consensus on management is needed if this is to be improved.